BIO-POTENT SULFONAMIDES - Selvakumar Dineshkumar; Ganesamoorthy Thirunarayanan (Journal of the Chilean Chemical Society, 2019)
Some 4-(substituted phenylsulfonamido)benzoic acids have been synthesized by fly-ash:H3PO3 nano catalyst catalyzed condensation of substituted benzenesulfonyl chlorides and 4-aminobenzoic acid in ultrasound irradiation conditions. The yields of the sulfonamides are more than 90%. The synthesized 4-(substituted phenylsulfonamido) benzoic acid derivatives were characterized by their physical constants, analytical and spectroscopic data. Antimicrobial activities of all sulfonamides were measured by Bauer-Kirby disc diffusion method.